Veronica persica Poir. extract – antibacterial, antifungal and scolicidal activities, and inhibitory potential on acetylcholinesterase, tyrosinase, lipoxygenase and xanthine oxidase - Sharifi-Rad, Javad; Tayeboon, Ghazaleh S; Niknam, Fereshteh; Sharifi-Rad, Majid; Mohajeri, Maryam; Salehi, Bahare; Iriti, Marcello; Sharifi-Rad, Mehdi (Cellular and Molecular Biology, 2018)
Veronica persica (Persian speedwell) is a flowering plant local to Eurasia. In this study, several analyses were done to discover the antimicrobial and scolicidal activities and acetyl cholinesterase (AChE), tyrosinase (TYR), lipoxygenase (LOX), and xanthine oxidase (XO) inhibitory activities of V. persica extract. The results presented that B. subtilis was the most susceptible to the extract (MIC = 40.3 Î¼g/mL), while P. aeruginosa was the most resistant strain (MIC = 250.9 Î¼g/mL) among all bacteria evaluated. The extracts demonstrated significant activity versus E. granulosus (P < 0.5) with dose-dependent inhibitions of the protoscolices. The analyzed plant extract exhibited a high AChE and TYR inhibitory activity 55.3% and 52.7% (at the highest utilized dose – 3 mg/mL), respectively. The extract also showed high anti-inflammatory activities in analyses tested. Our research proposed that extract of this plant could be promising to the human health, markedly in the infectious, neurodegenerative and inflammatory disorders.